Peculiarities of neurostimulation by intense nanosecond pulsed electric fields: how to avoid firing in peripheral nerve fibers - Kim, Vitalii (2021)
Intense pulsed electric fields (PEF) are a novel modality for the efficient and targeted ablation of tumors by electroporation. The major adverse side effects of PEF therapies are strong involuntary muscle contractions and pain. Nanosecond-range PEF (nsPEF) are less efficient at neurostimulation and can be employed to minimize such side effects. We quantified the impact of the electrode configuration, PEF strength (up to 20 kV/cm), repetition rate (up to 3 MHz), bi- and triphasic pulse shapes, and pulse duration (down to 10 ns) on eliciting compound action potentials (CAPs) in nerve fibers. The excitation thresholds for single unipolar but not bipolar stimuli followed the classic strength-duration dependence. The addition of the opposite polarity phase for nsPEF increased the excitation threshold, with symmetrical bipolar nsPEF being the least efficient. Stimulation by nsPEF bursts decreased the excitation threshold as a power function above a critical duty cycle of 0.1%. The threshold reduction was much weaker for symmetrical bipolar nsPEF. Supramaximal stimulation by high-rate nsPEF bursts elicited only a single CAP as long as the burst duration did not exceed the nerve refractory period. Such brief bursts of bipolar nsPEF could be the best choice to minimize neuromuscular stimulation in ablation therapies.